STRENGTHENING HALAL VALUE CHAIN AS A GUARANTEE OF HALAL PRODUCT AT SLAUGHTERHOUSES: CASE OF A CHICKEN SLAUGHTERHOUSE IN SEMBAYAT AREA - Hasanah, Niswatun; Sahliyah, Fatihatus; Alamsyah Harahap, Syamsir; Cathliniyah Zerlindah, Clairina (Universitas Muhammadiyah Surabaya, 2025)
This research aims to analyze the halal value chain of slaughter and processing in broiler chicken businesses at AFJ JAYA Sembayat from an Islamic economic perspective, as well as consumers' views of the halal value chain in these businesses. The research method used in this research is field research using a descriptive qualitative approach. Primary data was obtained through in-depth interviews with slaughterhouse managers and consumers. The results of the research show that the halal value chain practices for the chicken slaughter process at AFJ JAYA Sembayat comply with the provisions with MUI Fatwa Number 12 of 2009’s requirements concerning Halal Slaughter Certification Standards. However, chicken processing practices are not by the provisions of MUI Fatwa Number 12 of 2009 because they do not separate dirty and clean spaces. Due to business owners' ignorance of the significance of halal certification for the chicken slaughterhouse sector, AFJ JAYA Sembayat does not currently hold halal certification. However, consumers still choose to continue purchasing because they feel confident that the chicken meat is halal and high-quality. All of this is purely caused by a lack of halal literacy, so ongoing counseling and assistance are necessary.